Indacaterol/ Glycopyrronium in Symptomatic Patients with COPD (GOLD 2 and GOLD 3) Versus Salmeterol/ Fluticasone - Masud, Momina; Usman, Umar (Indus Journal of Bioscience Research, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a significant global health concern with increasing prevalence and substantial economic and social impacts. It is a leading cause of mortality, affecting millions worldwide. COPD severity is classified using the Global Initiative for Chronic Obstructive Lung Disease (GOLD) system, categorizing patients based on symptoms, airflow limitation, and exacerbation history. Treatment primarily involves long-acting bronchodilators, including LABAs and LAMAs. Indacaterol/glycopyrronium (IND/GLY) and salmeterol/fluticasone (SFC/FLU) are widely used therapies, however, direct comparisons remain limited. This study aims to compare IND/GLY and SFC/FLU in symptomatic COPD patients, evaluating their impact on symptom improvement using CAT scores. Methods: This was a randomized controlled trial conducted at Pulmonology Department, Allied-2 Hospital Faisalabad from 15 July 2024 to 15 January 2025. A total number of 266 patients were allocated to each treatment group. Outcomes were noted in terms of changes in the CAT score and the occurrence of adverse effects. Results: Of the 266 patients, 184 (69.2%) were male and 82 (30.8%) were female patients. Mean age of the patients was 48.16±6.81 years. Eighty-four (63.2%) patients had severe COPD. There was no significant difference in group-wise distribution of patients in both groups (p-0.265). Mean pretreatment CAT score was 28.49±4.311 in IND/GLY group and 28.86 ± 4.291 in SAL/FLU group. The post-treatment CAT score was 16.52 ± 3.378 in IND/GLY group and 16.97 ± 4.59 in SAL/FLU group. Conclusion: Salmeterol-fluticasone and indacaterol-glycopyrronium both improved lung function metrics and the quality of life in people with COPD while having little side effects. There was no significant difference in safety or effectiveness.